Comparison of high-intensity laser therapy and combination of ultrasound treatment and transcutaneous nerve stimulation on cervical pain associated with cervical disc herniation: A randomized trial - Yılmaz, Mustafa; Tarakcı, Devrim; Tarakcı, Ela (Churchill Livingstone, 2020)
The aim of the study was to compare the effect of high-intensity laser therapy (HILT) and a combination of transcutaneous nerve stimulation (TENS) and ultrasound (US) treatment on pain, range of motion (ROM) and functional activity on cervical pain associated with cervical disc herniation (CDH).A total of 40 patients (22 women and 18 men) affected by CDH were enrolled in this study. Patients were randomly divided into two groups. In group 1 (20 subjects), patients received 20 sessions of HILT plus exercise, while in group 2 (20 subjects), a combination of US, TENS and exercise were applied.The outcomes were cervical segment ROM, pain level measured by visual analogue scale (VAS), and functional activity measured by neck pain and disability scale (NPADS) before and after the therapy. The level of statistical significance was set as p < 0.05.There was no difference for cervical ROM, VAS and NPADS values between the groups at the baseline (p > 0.05). After the treatment, cervical ROM, VAS and NPADS values were significantly improved in both groups (p < 0.05). When the groups were compared in terms of post treatment VAS, NPADS and ROM values, no statistical significance was found between the two groups (p > 0.05).Both of therapeutic modalities demonstrated analgesic efficacy and improved the function in patients affected by CDH after 4 weeks of therapy (total 20 treatment sessions in 5 days a week).Both the HILT plus exercise program and the TENS / US plus exercise program were found to be effective in improving cervical range of motion and quality of life by reducing pain. These two treatment programs have similar effects in the treatment of cervical pain associated with CDH and can be used as an alternative to each other in clinical applications. However; It is clear that futher studies are needed to investigate the principles of application of HILT to painful areas or tissues (amount of area applied, dose applied, energy delivered, number of pulses, duration of session, frequency of sessions) and to exclude the effects of exercise treatment on the results of both treatment groups.
Keywords: Cervical Disc Herniation; High Intensity Laser Therapy; Neck Pain; Transcutaneous Nerve Stimulation; Ultrasound Treatment